Gambaran Kualitas Hidup Lanjut Usia Yang Mengalami Sakit Asam Urat (Gout) Di Posyandu Lanjut Usia Desa Pelemgadung Karangmalang Sragen - Rosyiani, Yunia Eka Tri, Agus Sudaryanto, S.Kep., Ns., M.Kes, Dewi Listyorini, S.Kep.,Ns (2015)
Gout as a type of inflammatory arthritis that are caused by deposition of uric crystals of sodium found in the synovial fluid. Uric acid (Gout) can cause a decrease in the quality of life for patients, because sufferers who experience uric acid will feel the pain so that interfere in the activity and comfort. The purpose of the research to know the description of the quality of life of seniors who experienced the pain of uric acid (gout). This research method using descriptive type which aimed to know the description of the quality of life of seniors who experienced the pain of uric acid (gout) with the approach of the approach of the survey. This research was conducted at the Posyandu seniors Village Pelemgadung Karangmalang Sragen and research time during July 2014. Populations and samples in this study was 40 elderly. Purposive sampling technique used sampling. The results of research that the description of the characteristics of the majority of the elderly aged 69-71 years, most are female gender, educational level is not the most educated, most marital status is mated, most work was as a farmer. The image of the elderly who experience uric acid based on the results of the measurement of uric acid values most respondents with a value of uric acid 6.1 - 7.0 mg/dl, while the results of the measurement of uric acid values of respondents the least value of uric acid 8.1 - 9.0 mg/dl. The image of the elderly to know the quality of his life get most respondents in the category are for all instruments WHOQOL-BREF consists of quality and health in General, physical health (domain 1), psychological (domain 2), social relations (3 domains), and environment (domain 4). The results of this research it can be concluded that the quality of life based on domains (health, psychology, and physical environment) are in a condition of being, whereas the domain social relationships in poor condition. Findings from this research should be more active elderly go to information (inform consent) about uric acid, with activities is expected to be able to understand the elderly care of gout.